Pengaruh Konsentrasi Asam Terhadap Aktivasi Lempung Palas Dan Aplikasinya Sebagai Katalis Pada Pembuatan Biodiesel Dari Minyak Nyamplung Dengan Variasi Kecepatan Pengadukan - Renia Navivin; Syaiful Bahri; Wisrayetti Wisrayetti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This study aims to produce biodiesel from calophyllum oil using acid-activated heterogene clay catalyst, determining catalyst and biodiesel characteristics and determining the selectivity of clay catalyst. The clay catalyst is prepared by grinding clay soil that has been dried to a size of -100 + 200 mesh, then clay is activated using H2SO4 0.5 N, 1 N and 2N solution. Then filtered using a vacuum pump. The solids are then calcined at 300ºC. The process of making biodiesel is carried out through two stages: esterification and transesterification, in transesterification process of stirring speed variation of 200 rpm, 300 rpm, 400 rpm, with catalyst weight of 3% by weight of oil, calophyllum oil sample weight 80 grams and methanol with ratio of oil to methanol 1: 12 is introduced into the transesterification reactor, the reaction lasting for 120 minutes at 60 ° C. This study yielded the largest biodiesel yield on 2 N activated acid catalyst with 400 rpm mixing speed velocity of 78.4%. Characteristics of the catalyst that has a surface area and ratio of Si / Al is large enough.Keywords: biodiesel, calophyllum, clay, transesterification.